Pyrolysis of Some Polyvinyl Polymers at Temperatures Up to 1,200 °C - Straus, Sidney (J Res Natl Bur Stand A Phys Chem, 1962)
A study was made of the thermal behavior in a vacuum of polystyrene, polytetraflu-oroethylene, poly(α-methylstyrene), polypropylene, polyisobutylene, and poly(methylmethacrylate), when pyrolized at 500, 800, and 1,200 °C. The volatile products of degradation were collected and fractionated, and the fractions analyzed by mass-spectrometric and microcryoscopic methods. Generally, the results from 500 °C pyrolysis resemble those obtained previously from the same polymer at lower temperatures. The results at 800° and 1,200° indicate a much greater fragmentation of the pyrolysis products than at lower temperatures. Thus, for example, at 1,200° polystyrene yields less monomer but considerable greater amounts of C(2)H(2), C(2)H(4), C(3)H(4), and C(6)H(6) than at lower temperatures. Similarly, poly (α-methylstyrene) yields 100 percent monomer below 500 °C, but at 800 and 1,200 °C the yields are 88 percent and 34 percent, respectively. Also at the higher temperatures, pronounced amounts of H(2), CH(4), C(2)H(2), C(2)H(4), C(3)H(4), C(3)H(6), C(4)H(4), C(6)H(6), C(4)H(8), and C(8)H(8) are formed.